2015
DOI: 10.1007/s12031-015-0633-3
|View full text |Cite
|
Sign up to set email alerts
|

Unfolded Protein Response Pathways in Neurodegenerative Diseases

Abstract: The aggregation of disease-specific misfolded proteins resulting in endoplasmic reticulum stress is associated with early pathological events in many neurodegenerative diseases, and apoptotic signaling is initiated when the stress goes beyond the maximum threshold level of endoplasmic reticulum stress sensors. All eukaryotic cells respond to the accumulation of unfolded proteins in the endoplasmic reticulum (ER) by signaling an adaptive pathway termed as unfolded protein response (UPR). Recently, the focus of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 87 publications
(93 reference statements)
0
25
0
Order By: Relevance
“…There are three mechanistically distinct branches of the UPR. Each branch begins with a specialized stress sensor located at the ER membrane: inositol requiring enzyme 1 (IRE1), double stranded RNA-activated protein kinase (PKR)-like ER kinase (PERK), and activating transcription factor 6 (ATF6; Figure 1; Shah et al, 2015). The first branch of the UPR relies on the dimerization of IRE1 and its autophosphorylation to initiate a signaling cascade mediated through the transcription factor X-box binding protein 1 (XBP-1) to upregulate a subset of the UPR related genes involved in the protein folding processes and the ERAD (Mays and Soto, 2016).…”
Section: Unfolded Protein Response In Prion Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…There are three mechanistically distinct branches of the UPR. Each branch begins with a specialized stress sensor located at the ER membrane: inositol requiring enzyme 1 (IRE1), double stranded RNA-activated protein kinase (PKR)-like ER kinase (PERK), and activating transcription factor 6 (ATF6; Figure 1; Shah et al, 2015). The first branch of the UPR relies on the dimerization of IRE1 and its autophosphorylation to initiate a signaling cascade mediated through the transcription factor X-box binding protein 1 (XBP-1) to upregulate a subset of the UPR related genes involved in the protein folding processes and the ERAD (Mays and Soto, 2016).…”
Section: Unfolded Protein Response In Prion Diseasesmentioning
confidence: 99%
“…The main purpose of the PERK pathway signaling cascade is to relieve the ER stress by reducing the amount of proteins entering the ER (Shah et al, 2015). Moreno et al (2012) have shown that PERK pathway took an active part during prion infection of the wild type mice and all the hippocampi of prion-infected wild type mice and those overexpressing PrP c had activated PERK branch of the UPR.…”
Section: Unfolded Protein Response In Prion Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, the upregulation of ERS-related transcription factors, including glucose-regulated protein (GRP)78 and CCAAT-enhancer-binding homologous protein (CHOP) have been identified (11,12). The involvement of ERS has been widely observed in the brain pathogenesis of neurological disorders and neurodegenerative diseases, including cerebral ischemia, Alzheimer's disease, Parkinson's disease and amyotrophic lateral sclerosis (9,13,14). Nonetheless, to the best of Edaravone improves spatial memory and modulates endoplasmic reticulum stress-mediated apoptosis after abdominal surgery in mice our knowledge, the regulatory role of ERS in the brain damage of POCD has not been described.…”
Section: Introductionmentioning
confidence: 99%
“…During activation of the UPR, the IRE1 RNase cleaves Xbp1 mRNA to remove a 26-nucleotide intron, which creates a translational frame shift to generate a large form of Xbp1. This Xbp1 contains a novel transcriptional activation in its C-terminus [4373]. The sXbp1 acts as a transcriptional activator that has a major role in the activation of a wide variety of UPR target genes, which include some genes that require the IRE1/Xbp1 pathway and encode proteins that function in ERAD [164387].…”
Section: Ros Mediated Upr Signaling Pathways In Preimplantation Embryosmentioning
confidence: 99%